Significado do cuidado familiar à mulher mastectomizada - Bonfim, Isabela Melo (2008)
The breast cancer used to be reason of fear between the women and in all the society, in general. The simple pronunciation of the word cancer, already generates in the feminine population feeling of fear, sadness, anxiety and negation, which had to the raised index of morbid-mortality and also of decurrent mutilation of the illness, that always compromises the auto-esteem, the social interaction, the affective relationships and the professional life of who it is under attack. It enters the familiar ones of the patients with cancer, is not different. The feelings and reactions generated ahead of the confirmation of if having a relative with mammary neoplasms, cause a series of feelings that many times modify all the familiar dynamics. The doubts, questionings, changes of papers and alterations in the routine of the family, are frequent and many times, the psychological unpreparedness to deal with the new condition of the dear person, bring doubts and frustrations. Therefore, to know of that way these families deal with the fact of if having a with mammary neoplasms, it was the fidget that motivated the accomplishment of this study, that had as objectives to discovering the meanings that the families of mastectomized women construct and that they guide its action when taking care of it and to present a theoretical model concerning the care given for the families to the mastectomized woman. One is about a descriptive study with qualitative boarding that it used as review theoretician the Symbolic Interactionism and the Theory Based on data Grounded Teory as frameworks metodological. The collection of data happened in the month of July of 2008, in an institution of reference in the treatment of the cancer. We use as strategy for the collection of data, the interview with eleven family caregivers ones of mastectomized women. We got then, the data that after the analysis, had allowed the creation of the central theory: Meaning of the familiary care to the mastectomized woman, which consists of distinct phenomena that if across: Understanding of the family on the mastectomy, that it is characterized disclosing as the family if it feels ahead of a family caregivers one with cancer and when taking care of a mastectomized woman; The difficulties of the family to take care of, whose purpose is to demonstrate the occured changes in the family, are they, financial or in the modified familiar social paper; Understanding the diagnosis of cancer in the family, where it is perceived dimension of the impact of the diagnosis of the breast cancer, reaching not only the woman, but all the familial sinus and the familiar care after the surgery, that emphasizes as woman and family searchs to surpass the limitations while people interacting in the familiar group under attack by the breast cancer. In our opinion, the care in family requires the true and affectionate envolvement, to become involved themselves and to believe that its presence is so important how much the accomplishment of procedures technician. As we stand out, nor always the objective knowledge technician function so well ahead of situations of stress as the subjective knowledge that if disclose in the familiar dynamics.